Predictive Ability of the Index of Creditworthiness - Kuběnka Michal (Univerzita Tomáše Bati ve Zlíně, 2015)
The creditworthy models shall define the level of financial health of analysed economic entity. As well as the bankruptcy models the creditworthy models are usually made of a combination of chosen ratio indexes and assigned weights. Models are, in several cases, based on the points system. In case of bankruptcy models the accuracy of their prediction can be verified on samples of companies that went into the insolvency or even bankrupted. The question is how to evaluate the accuracy of creditworthiness models evaluation. This text presents the created methodology and results of research focused on the creditworthiness index accuracy evaluation. The goal is to set the index of creditworthiness accuracy on the base of own methodology. For this purpose the economic data of 1260 companies from the processing industry sphere were analyzed.
Predikční schopnost Indexu Bonity
Keywords: creditworthiness; index of creditworthiness; creditworthy models; ROE; implicit costs; EVA; bonita; index bonity; bonitní modely; ROE; implicitní náklady; EVA